Proceedings of the ACM/IEEE International Conference on Human-Robot Interaction 2007
DOI: 10.1145/1228716.1228753
|View full text |Cite
|
Sign up to set email alerts
|

Influence of perspective-taking and mental rotation abilities in space teleoperation

Abstract: Operator performance during Space Shuttle and International Space Station robotic arm training can differ dramatically among astronauts. The difficulty making appropriate camera selections and accurate use of hand controllers, two of the more important aspects for performance, may be rooted in a problem mentally relating the various reference frames used by the displays, hand controllers and robot arm. In this paper, we examine whether the origin of such individual differences can be found in certain component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 15 publications
1
35
0
Order By: Relevance
“…This was demonstrated through a task that, we felt, had real-life relevance, since it involves skills that might be used by cartographers or hikers in their respective activities. Accordingly, the present results can be added to the body of evidence demonstrating that tasks with real-life applicability relate to psychometric test performance (Hambrick et al, 2012;Liu, Oman, Natapoff, & Coleman, 2008;Menchaca-Brandan, Liu, Oman, & Natapoff, 2007).…”
Section: Discussionmentioning
confidence: 67%
“…This was demonstrated through a task that, we felt, had real-life relevance, since it involves skills that might be used by cartographers or hikers in their respective activities. Accordingly, the present results can be added to the body of evidence demonstrating that tasks with real-life applicability relate to psychometric test performance (Hambrick et al, 2012;Liu, Oman, Natapoff, & Coleman, 2008;Menchaca-Brandan, Liu, Oman, & Natapoff, 2007).…”
Section: Discussionmentioning
confidence: 67%
“…In such a case, the operator constantly sends control commands to the robot in the same manner, however, robot movement directions could vary depending on the robot's current orientation at any given point of time. The operator has to deal with this mental rotation problem [17]. The operator has to predict the robot's movement direction, convert it to input direction and control the joystick accordingly.…”
Section: Problem Of Unpredictability Of the Results Of The Remotementioning
confidence: 99%
“…SpA has been found to be a significant factor in virtual environment navigation (Stanney & Salvendy, 1995), learning to use a medical teleoperation device (Eyal & Tendick, 2001), target search task (Chen et al, 2008;Chen & Joyner, 2009), and robotics task performance (Cassenti et al, 2009;Lathan & Tracey, 2002;Menchaca-Brandan et al, 2007). For example, Lathan and Tracey (2002) demonstrated that people with higher SpA performed better in a teleoperation task through a maze.…”
Section: Individual Differences In Spatial Ability and Attentional Comentioning
confidence: 99%